Photochemistry for Biomedical Applications From Device Fabrication to Diagnosis and Therapy (Springer Singapore, 2018)
This book describes medical applications of photochemistry. In the first part, a general introduction to photochemistry and related phototechnologies is provided. In the second part, photochemistry-based medical applications for diagnostics (biochips and bioimaging) and therapeutics (biomaterials for artificial organs, medical adhesives, dental materials, drug-delivery systems, tissue engineering, and photodynamic therapy) are described, with examples of recent research. The year 2015 is the International Year of Light and Light-Based Technologies. Light plays a vital role in our daily lives and is important in many interdisciplinary scientific fields in the twenty-first century. Light-based concepts have revolutionized medicine, including areas such as oncology, molecular biology, and surgery. Although photochemistry has contributed significantly to medicine directly and through photochemical fabrication of biomaterials, a book giving a comprehensive overview of recent progress has not been published until now. The aim of this book is to highlight the contributions of photochemistry in interdisciplinary fields of chemistry and medical engineering. This book will be useful for chemists who are interested in medical applications of photochemistry and engineers who are eager to learn the principles of photochemistry to enable its use in practical applications.